Consumer Perception of Visual Innovation in China Time-Honored Brands: A Conceptual Paper - Fan, Xinying; Ismail, Adzrool Idzwan (UUM Press, 2023)
China time-honored brands have been favored by consumers because of their unique cultural attributes. In the era of modern commerce, China has numerous time-honored brands. Yet, very few of them remain evergreen and thrive consistently over time. Therefore, it is very important to explore the innovative ways of China time-honored brands. After reviewed the research of China time-honored brands and existing literature on consumers' perception of brand visual innovation, this work obtained the function diagram of the visual innovation of brands perceived by consumers. This perception pertains to consumers' recognition of the visual imagery, craftsmanship, innovative services, and creativity of these brands, as well as the perception of whether there will be ongoing innovative activities and potential for innovation in the future. On this basis, combined with the characteristics of China time-honored brands, the theoretical model proposed in this paper can further develop the measurement of consumer perception of the visual innovation of China time-honored brands in the future, and carry out empirical research to provide theoretical support for the revitalization of China time-honored brands.